An introduction to sensitivity assessment of simulation models. (July 2015) - Norton, John
Abstract: In view of increasing application of sensitivity assessment (SA) to environmental simulation models, a relatively short, informal introduction to aims and methods of SA is given. Their variety, motivation and scope are illustrated by outlines of a broad selection of approaches. Methods based on derivatives, algebraic analysis, sparse sampling, variance decomposition, Fourier analysis and binary classification are included. Highlights: A concise introductory overview of sensitivity assessment (SA) methods for simulation models is given. A broad selection of methods is introduced informally and with no more mathematics than necessary. The motivation of the methods, their scope and their limitations are discussed. Derivative-based SA, algebraic SA, SA of dynamical models, sampled SA, regional SA and SA by emulation are outlined.